Respostas
respondido por:
3
4x/6 - 2x + 3 = 11 - 4x (6)
4x - 12x + 18 = 66 - 24x
-8x + 18 = 66 - 24x
-8x + 24x = 66 - 18
16x = 48
x = 48 / 16
x = 3
obs. multiplicando a conta toda por 6 , para desfazer a fração 4x/6
Resposta: x = 3
4x - 12x + 18 = 66 - 24x
-8x + 18 = 66 - 24x
-8x + 24x = 66 - 18
16x = 48
x = 48 / 16
x = 3
obs. multiplicando a conta toda por 6 , para desfazer a fração 4x/6
Resposta: x = 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás